(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the concept of the national-cultural code as reflected in language and media discourse. It emphasizes the role of language in transmitting cultural values, traditions, and worldview across generations. The study analyzes linguistic means representing cultural codes in Uzbek, Russian, and English online media, revealing both semantic equivalence and cultural specificity. Drawing on the works of prominent linguists and semioticians, the article discusses the theoretical foundations of cultural codes, their classifications, and their role in shaping national identity. The research highlights the symbolic nature of cultural codes, which are manifested through rituals, myths, traditions, and media texts.